Prospective evaluation of ottawa ankle rules in acute ankle injury - Saleh, Ramzi Ali (2013)
Acute ankle injuries are one of the most common reasons for presenting to emergency departments. These patients are almost always routinely referred for radiography, whereas less than 15% have clinically significant fractures. The Ottawa Ankle Rules (OARs) have been designed to reduce the number of unnecessary radiographs ordered for these patients. To evaluate the OAR for predicting ankle and/or midfoot fractures in Malaysian population whose sustained acute ankle injuries. This prospective survey was conducted in the emergency department and orthopedic clinic of hospital university sains of Malaysia. The study group consisted of 73 patients aged 18 years and older who presented with acute ankle and/or midfoot injuries during 12 months. Radiography was performed for all patients after clinical evaluation findings were recorded. Main outcome measures of this survey were: sensitivity, specificity, positive predictive value, negative predictive value, and likelihood ratios (positive and negative) of the OARs. Twenty two ankle and 12 midfoot fractures were diagnosed. The decision rules had a sensitivity of 100% a specificity of 73.68% and a negative predictive value of 100% in detecting ankle fractures, a sensitivity of 100%, a specificity of 84.61%, and a negative predictive value of 100% in detecting midfoot fractures. Implementation of the OARs had the potential for reducing radiographs by 42.4%. OARs are very accurate and highly sensitive tools for detecting ankle fractures. Implementation of these rules in our population would lead to significant reduction in the number of requesting for radiographs without missing any clinically significant fractures, thus reducing costs, radiation exposure and waiting times in emergency departments.